Guidelines for kidney cancer. Part I: Epidemiology, diagnosis, surgical treatment - Borówka, Andrzej; Szcześniak, Cezary (Contemporary Oncology/Współczesna Onkologia, 2004)
Renal cancer represents 3.6% of all malignant neoplasms in men and 2.6% in women. The most frequent among them is renal cell carcinoma. Typical symptoms are palpable tumor, pain and haematuria. This triad occurs in approximately 10% of patients with renal cancer. More than 50% of tumors are diagnosed by chance by ultrasound examination made for other reasons. The only solid renal cancer that could be reliably diagnosed preoperatively by imaging techniques is angiomyolipoma (AML). The other solid tumors are treated as potentially malignant, because mostly they are renal cancers. After their diagnosis the imaging examination should be performed to evaluate the stage of the disease. The most important treatment method is surgery that involves total nephrectomy with lipid capsule and Gorot fascia. Adrenal glands should also be removed, if the renal tumor originates from the upper pole and is invading or is suspected to invade the adrenal gland. Regional lymphadenectomy is usually performed to estimate possible metastases to them. In the case of a tumor of a meaningful diameter or tumor with neoplastic emboli coming up to the inferior vena cava radical extraperitoneal nephrectomy is performed. When the tumor is small (diameter less than 4 cm) kidney conserving surgery is possible. It involves tumor removal with cancer-free margin. The efficacy of such treatment is comparable to radical nephrectomy.